Wasting Food Practice on Tiktok: Micro-Fame, Profit, and Trendiness - Alfi Syahriyani; Ismi Ana Nurazizah; Anzalas Sakinata; Andini Suandi Putri (LONTAR: Jurnal Ilmu Komunikasi, 2023)
This research aims to investigate the phenomenon of wasting food practice, which once became a trend on TikTok, during pandemic era. This study utilizes a qualitative method with elaboration and literature review on several research related to the issue. The analysis revealed that the emergence of wasting food content trends on TikTok was related to the coherence between globalization as the root of the era of technological progress, the ideology of capitalism driven by changes in people's mindsets, and active participatory culture as capitalist behavior that promotes the wasting food content for the sake of individual satisfaction (fame and trendiness) and profit. This study also concluded that TikTok served as the social media which offered public benefit in the form of creative video content that might violate the social norms.